2020
DOI: 10.1002/jhbp.812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chelation therapy in pediatric Wilson’s disease: Liver and endoscopic outcome

Abstract: Background As there is paucity of exclusive literature on pediatric hepatic Wilson's disease (WD), this study was undertaken to evaluate the efficacy of chelation on hepatocellular function and portal hypertension in WD. Methods Wilson's disease patients with ≥9 months of follow‐up were evaluated for response to chelation therapy in the following categories: (a) complete remission, (b) partial remission (c) progression of disease; (d) drug toxicity. Pediatric end‐stage liver disease (PELD), Nazar and New Wilso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Only 2 (5.88%) of them were started on trientine because of bone marrow suppression. To date, over a mean period of 10 years, none of the patients in the present study who underwent chelation therapy have required LT. Our results are supported by studies from neighboring countries like India, where chelation therapy with penicillamine has shown good results, even in patients with severe hepatic disease [ 19 ]. Another study from India reported the adjunctive role of zinc therapy in pediatric WD, with good outcomes [ 20 ].…”
Section: Discussionsupporting
confidence: 85%
“…Only 2 (5.88%) of them were started on trientine because of bone marrow suppression. To date, over a mean period of 10 years, none of the patients in the present study who underwent chelation therapy have required LT. Our results are supported by studies from neighboring countries like India, where chelation therapy with penicillamine has shown good results, even in patients with severe hepatic disease [ 19 ]. Another study from India reported the adjunctive role of zinc therapy in pediatric WD, with good outcomes [ 20 ].…”
Section: Discussionsupporting
confidence: 85%
“…Its fundamental purpose is to restore the function of ATP7B -mediated hepatic and bile duct excretion of copper ( Murillo et al, 2016 ), and it may be the most promising treatment in the future. The incidence of acute liver failure in WD has previously been reported to be 15–47% ( Das et al, 2021 ; Devarbhavi et al, 2014 ; Rukunuzzaman, 2015 ). Among the successful follow-up cases in this group, except for one case (3.3%) with liver failure, the liver function recovered well after the application of penicillamine, oral zinc preparations, B vitamins, and low-copper diet, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical parameters like serum albumin, total bilirubin and prothrombin time normalizes by 6 mo but liver enzymes might take longer[ 12 ]. In the author’s experience it takes 9-12 mo for complete normalization of Liver function tests in majority of the cases[ 50 ]. In patients who have additional neurological involvement, neurological response is monitored by indices such as Global assessment scale (GAS)[ 51 ].…”
Section: Chelation In Wdmentioning
confidence: 99%
“…77% of children responded to DPA monotherapy even when the disease is severe at presentation and 50% responded when DPA and zinc combination was started. The overall response to oral chelation is 71%[ 50 ]. Hence, DPA should be the first line of therapy for any hepatic WD and zinc is added in those who failed to show optimal response with DPA in desperate circumstances with the hope of rapid synergistic chelation and quicker liver recuperation[ 50 ].…”
Section: Chelation In Wdmentioning
confidence: 99%
See 1 more Smart Citation